2012
DOI: 10.1007/s00221-012-3338-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of speeding up or slowing down animate or inanimate motions on timing

Abstract: It has recently been suggested that time perception and motor timing are influenced by the presence of biological movements and animacy in the visual scene. Here, we investigated the interactions among timing, speed and animacy in two experiments. In Experiment 1, observers had to press a button in synchrony with the landing of a falling ball while a dancer or a whirligig moved in the background of the scene. The speed of these two characters was artificially changed across sessions. We found striking differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Consistent with this hypothesis, there is evidence that time perception and motor timing are influenced by animacy: the observation of a biological movement performed by other people biases the timing of a motor act or the judgment of perceived duration of an event (Watanabe, 2008; Bove et al, 2009; Carrozzo et al, 2010; Orgs and Haggard, 2011; Zago et al, 2011b,c; Mouta et al, 2012; Wang and Jiang, 2012; Carrozzo and Lacquaniti, 2013). In particular, Carrozzo et al (2010) used interference paradigms in which a timing task was run concurrently with the presentation of different figures animated with computer-graphics in the background of the scene ( Figures 4A,B ).…”
Section: Observation Of Biological Motionmentioning
confidence: 83%
See 2 more Smart Citations
“…Consistent with this hypothesis, there is evidence that time perception and motor timing are influenced by animacy: the observation of a biological movement performed by other people biases the timing of a motor act or the judgment of perceived duration of an event (Watanabe, 2008; Bove et al, 2009; Carrozzo et al, 2010; Orgs and Haggard, 2011; Zago et al, 2011b,c; Mouta et al, 2012; Wang and Jiang, 2012; Carrozzo and Lacquaniti, 2013). In particular, Carrozzo et al (2010) used interference paradigms in which a timing task was run concurrently with the presentation of different figures animated with computer-graphics in the background of the scene ( Figures 4A,B ).…”
Section: Observation Of Biological Motionmentioning
confidence: 83%
“…Carrozzo et al (2010) found that, for both the motor interception and the time discrimination task, there was a systematic offset between the time estimates associated with biological movements and the time estimates associated with non-biological movements, consistent with the hypothesis that there exist timing mechanisms differentially tuned to these two sets of movements. In another study, the speed of the movements of the background figures was varied across sessions, so that the motion speed of all the segments of the character was scaled up or down by the same amount and to the same extent for both the biological and the non-biological figure (Carrozzo and Lacquaniti, 2013). The results confirmed the existence of an offset between the time estimates associated with biological movements and the time estimates associated with non-biological movements ( Figure 4 ).…”
Section: Observation Of Biological Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, static and dynamic representations of the human body can also generate temporal distortions [16,17]. Apparent biological motion, particularly regarding the shape of the human body, is thought to induce specific distortions in time perception [18][19][20][21][22][23]. Nather and Bueno suggested that the perceived duration of symmetrical representations of the human body (sculptures) tended to be temporally underestimated compared to asymmetrical body sculptures [16].…”
Section: Introductionmentioning
confidence: 99%
“…The perceived duration of intervals of hundreds of milliseconds to a few seconds—a time scale in which many daily live actions unfold—is distorted by the dynamics of visual stimulation 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 . It is unclear, however, which aspect of the dynamics is critical in perceived duration distortions and hence, which are the underpinning mechanisms and possible function of such distortions.…”
mentioning
confidence: 99%